The Effect Of Using Picture Word Inductive Model (PWIM) Towards Students’Writing Ability In Descriptive Text At Tenth Grade Students Of SMAN 9 Mandau - Musfiroh (Jolly Journal of English Education, 2024)
This study was carried out find out. The Effect Of Using Picture Word Inductive Model (PWIM) Toward Student’s Writing Ability in Descriptive Text at Tenth Grade of SMAN 9 Mandau.”. The descriptive quantitative was applied to describe data, with a quasi-experimental research. The study population was all 336 students in grade X consisting of 9 classes. Due to the large population, the researcher  took a sample of 70 students using cluster random sampling technique. In this study, the average pre-test score for the experimental class was 65.74 and the control class was 54.85. Meanwhile, the average post-test score of the experimental class was 76.58 and the control class was 68.62. Based on the probability scores gathered from SPSS 22, it was shown that the sig. (2-tailed) value for Pair 1 was 0.000 < 0.05. This indicated that there were significant differences in the average students’ writing ability between the pre-test and post-test. This meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected)